PHYSICAL AND CHEMICAL ATTRIBUTES AND CARBON STOCKS IN A YELLOW ACRISOL IN DISTINCT USE AND MANAGEMENT SYSTEMS IN WESTERN AMAZON - Brito, Erbesson Souza; Muetanene, Belo Afonso; Junior, Elizio Ferreira Frade; Alassane, Daibou; AraÃºjo, Edson Alves de (REVISTA DE AGRICULTURA, 2022)
Â Understanding and measuring the impacts of soil use and management systems on the soil physical, chemical properties and carbon stocks is fundamental for the development of sustainable systems in Western AmazÃ´nia. The present study evaluated the alterations in the soil physical, chemical properties, and carbon stocks after the substitution of a native forest (NF) into a pasture (PAST) and agroforestry system (AS) in a yellow Acrisol. In each soil use system, we opened four pits to collect soil samples with preserved structure, for the determination of soil bulk density (BD). We also collected samples with altered structure, for the determination of soil total organic carbon, pH (H2O), Ca2+, Mg2+, K+, P, remaining P, Al3+ and H+Al at the 0-5, 5-10, 10-15, 15-20, 20-30, 30-40 and 40-50 cm layers. The change in the soil use system from the NF, independently on the agroecosystem (PAST or AS), increased the soil bulk density values, mainly at the 5 to 20 cm layers, with higher values in the PAST. The nutrients evaluated and the soil total organic carbon presented low concentrations, being increased by the soil use change from the NF to PAST and AS. Thus, the basic cations and the available P are below the minimum thresholds and concentrated at the Â soil first layers. The PAST and AS increased the concentrations of these basic cations, and the soil carbon stock was not altered when compared to the NF, however, there was an increase in the soil bulk density, this increase was more profound in the PAST. Â Keywords: Acre, agroforestry system, native forest, pasture, soil conservation